Chapter Da Antero de Quental a Mário Soares: dal pensiero alla politica sociale nella vertigine della democrazia portoghese - Pereira, António dos Santos (Libere carte, 2023)
The future has always been the destiny of men of action. We note the roots of the thought and fiction of the Portuguese socialist leader, Mário Soares, in the references of the political thought of Antero de Quental and the pedagogical of António Sérgio for the economic, social, cultural and mental well-being of the Portuguese people that we make coincide with humanity because western humanism movesus.